A Magical Rock Crystal Gem from Apollonia-Arsūf, Israel. (14th January 2019) - Heidemann, Stefan; Zeischka-Kenzler, Annette; Tal, Oren
Abstract : This article discusses an inscribed large crystal rock gem (2.70 x 2.15 x 1.65 cm), retrieved during the excavations at Apollonia-Arsūf. It bears a two-line magical inscription written in linear Kūfic script. It is the first magical rock crystal ever found in a proper archaeological context. Based on its appearance, it can only be vaguely dated between the eighth to the twelfth centuries. A late date would make it contemporary to the associated ceramics in that layer. The relative proximity of the find place to Egypt makes an origin of the talisman from Fāṭimid Egypt likely, as may also be suggested in our analytical appendix.